Brian Moore’s Fergus: A Baudrillardian Reading - Salehnia, Atefeh; Pirnajmuddin, Hossein (Mediterranean Journal of Social Sciences, 2012)
Postmodern literature is founded upon the assumption that the symbolic order of the pre-capitalist era has been transformedby mass media and information technologies into a society inundated with decontextualized signs. Fragmentation of authentic meanings,eclipse of real objects by ‘hyperreality’ and dissolution of subjectivity, identity and religion are grounded, according to Jean Baudrillard, inthe contemporary ‘semiurgic’ culture. The present paper aims at examining the applicability of Baudrillard’s ideas concerning thedominant cultural atmosphere in the postmodern era to Brian Moore’s Fergus (1970). In Moore’s novel a consumerist society isdelineated in which the infinitely reproduced objects and commodities threaten the individuality and identity of modern man. Besides, thenovel depicts a world in which the ‘auratic’ value of art, human relations and religion are replaced by their simulated counterparts.